IMPACT OF DIGITAL TRANSFORMATIONS ON PUBLIC SERVICES - BRECHKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
One of the strategic goals of the Ministry of Digital Transformation of Ukraine is to transfer 90% of public services to an online format by 2024 so that the majority of Ukrainians can use online services and other digital products. Providing public services in an online format increases their accessibility for the population, saves resources of the state and communities, reduces the influence of the "human" factor and reduces corruption risks. In Ukraine, a lot of work has already been done in this direction: a large number of public services have been transferred to the online format, mobile applications have been developed for them, and work is underway to popularize their use among the population. However, a number of issues related to the integration of existing and new services into a single web portal and increasing the level of digital literacy of the population remain unsolved. Such a situation actualizes the topic of the selected research. Purpose of the study is to study the impact of digital transformations on the sphere of public services of the national economy. The research hypothesis is the interpretation of the digital economy as an important tool for increasing the availability of public services for various population groups and promoting their inclusiveness. In the process of research, methods of a system approach and data summarization were used to study the impact of digital transformations on the sphere of public services. In addition, general scientific and empirical methods and tools of economic science, methods of analysis and synthesis, comparison, summary and grouping were used. The processes of penetration of digital technologies into the system of providing public services at the regional level have been studied, the most popular types of public services that can be obtained today with the help of digital technologies have been singled out: SRCSA services (state registration of civil status acts); registration of FOP; accrual for registration of e-pensions; electronic driver’s office; HELSI (doctor’s appointment, medical card, e-prescriptions and treatment plan); state land cadaster, etc. During the research, it was established that the vast majority of the analyzed types of electronic services were integrated into «Dia». But there are still a number of electronic services that work autonomously. It is proposed to focus further development of the field of electronic services on: systematic expansion of the list of services provided online; integration of online services for the provision of electronic services into a single portal «Dia»; system modernization of the mobile application of the single portal «Dia» taking into account innovations; increasing the level of cyber security; expanding the possibility of connecting to the Internet; increasing the level of digital literacy of citizens. Further research should be focused on assessing the level of accessibility and quality of electronic public services.